Ride Like the Wind: Equestrian Sport in Hellenistic and Early Imperial Rhodes - Papakonstantinou, Zinon (Classica et Mediaevalia, 2026)
During the Hellenistic and early Imperial periods Rhodes had a vibrant athletic culture, with numerous agonistic festivals. In keeping with the trend throughout the Greek-speaking world which suggests a diminished presence of hippic sport in Greek games, especially beyond the periodos contests and some prominent local festivals, equestrian competitions are attested in Rhodes only for the Great Halieia. Notwithstanding this trend, Rhodian elites maintained a keen interest in breeding, training, and racing horses throughout this period. Victories were commemorated at the sites of competition, especially regarding major interstate games, as well as in sanctuaries and other prominent sites in Rhodes. Moreover, a substantial body of evidence strongly suggests that, contrary to scholarly orthodoxy, frequently Rhodian elites engaged in equestrian sport from a young age, usually starting in their twenties, and hence at the outset of their public service careers.